Urban Watershed Services For Improved Ecosystem Management and Risk Reduction, Assessment Methods and Policy Instruments: State of the Art - Yaella Depietri; Lorenzo Guadagno; Margaretha Breil (Fondazione Eni Enrico Mattei (FEEM), 2013)
Under scenarios of increasing unplanned urban expansion, environmental degradation and hazard exposure, the vulnerability of urban populations, especially of their poorer segments, needs to be tackled through integrated economic, social and environmental solutions. Basing our analysis on the concept of ecosystem services, we suggest that urban areas would benefit from a shift in perspective towards a more regional approach, which recognizes them as one of many interconnected elements that interact at the watershed level. By integrating an ecosystem approach into the management of water-related services, urban management policies can take a first step towards fostering an improvement of the health of upstream and downstream areas of the watershed, activating environmentally sound practices which aim at guaranteeing the sustainable and cost effective supply of services. These strategies can for instance be supported by using payment schemes for ecosystem services or similar strategies, allowing for the redistribution of resources among communities in the watershed. From our analysis it results that, through the recognition of the primary role played by watershed ecosystems, cities can benefit from an enlarged set of policies, which can help strengthen the supply of essential environmental services, while reducing the vulnerability of its population and contributing to the maintenance of healthy ecosystems.
Keywords: I14; Q01; Q25; Q54; Q57; 330; Urban Watersheds; Ecosystem Services; Water Supply And Sanitation; Disaster Risk Reduction; Valuation